Equivalent circuit modeling of the bistable conduction characteristics in electroformed thin dielectric films. Issue 1 (January 2015) - Blasco, J.; Ghenzi, N.; Suñé, J.; Levy, P.; Miranda, E.
Abstract: In the last few years a number of models based on simple circuital representations have been proposed to account for the resistive switching (RS) current–voltage ( I – V ) characteristics of metal–insulator–metal (MIM) structures. These devices typically exhibit two well-defined conduction levels after electroforming often referred to as the low and high resistance states that can be cyclically reached by the application of bipolar periodic voltage or current. The resulting hysteretic behavior arises from a reversible change of the electron transmission properties of the insulating film driven by an external stimulus. In this paper, after an overview of a variety of RS model proposals relying on circuital descriptions and basic analytic expressions, a model based on the solution of the generalized diode equation is discussed. The model is simple and flexible and consists of two opposite-biased diodes with series and shunt resistances that represent the filamentary current pathway spanning the oxide layer as well as the possible parasitic effects. The model parameters are governed by a mathematical entity called the logistic hysteron that can be linked to the internal state equation of the so-called memristive systems. For illustrative purposes, the switching I – V characteristics of TiO2 -based MIM structures electroformed with different current compliances are examined in detail using this approach. Experimental results on bipolar RS by other authors are also assessed within the same framework.